The Arithmetic of Emotion: Integration of Incidental and Integral Affect in Judgments and Decisions - Västfjäll, Daniel; Slovic, Paul; Burns, William J.; Erlandsson, Arvid; Koppel, Lina; Asutay, Erkin; Tinghög, Gustav (Frontiers in Psychology, 2016)
Research has demonstrated that two types of affect have an influence on judgment and decision making: incidental affect (affect unrelated to a judgment or decision such as a mood) and integral affect (affect that is part of the perceiver’s internal representation of the option or target under consideration). So far, these two lines of research have seldom crossed so that knowledge concerning their combined effects is largely missing. To fill this gap, the present review highlights differences and similarities between integral and incidental affect. Further, common and unique mechanisms that enable these two types of affect to influence judgment and choices are identified. Finally, some basic principles for affect integration when the two sources co-occur are outlined. These principles are discussed in relation to existing work that has focused on incidental or integral affect but not both.